2019
DOI: 10.3389/fmicb.2019.02791
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Tolerant Plant Growth Promoting Rhizobacteria for Enhancing Crop Productivity of Saline Soils

Abstract: Soil salinity has emerged as a serious issue for global food security. It is estimated that currently about 62 million hectares or 20 percent of the world's irrigated land is affected by salinity. The deposition of an excess amount of soluble salt in cultivable land directly affects crop yields. The uptake of high amount of salt inhibits diverse physiological and metabolic processes of plants even impacting their survival. The conventional methods of reclamation of saline soil which involve scraping, flushing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
227
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 399 publications
(235 citation statements)
references
References 193 publications
(175 reference statements)
6
227
1
1
Order By: Relevance
“…In the last few decades, anthropogenic activities have exacerbated the rate of soil salinization [1] , [2] . Saline soils are high in electrical conductivity (EC), low in water potential and excessive in amounts of ionic salts making survival of plant and other life forms difficult [3] , [4] . It is estimated that salinity has affected over 800 million hectares of agricultural land around the globe [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, anthropogenic activities have exacerbated the rate of soil salinization [1] , [2] . Saline soils are high in electrical conductivity (EC), low in water potential and excessive in amounts of ionic salts making survival of plant and other life forms difficult [3] , [4] . It is estimated that salinity has affected over 800 million hectares of agricultural land around the globe [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Physical methods of treatment of saline soils, that include flushing, leaching, scraping and chemical amendments e.g. addition of gypsum and lime, are not sustainable [4] . Soil flushing and scraping has achieved only a little success and has limited practical significance as the salt accumulation tends to resurface due to lowering of water table and the problem intensifies with course of time.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that seed inoculation with microbes capable of indole-3-acetic acid (IAA) secretion efficiently improved plant tolerance to salt stress [ 30 , 31 , 32 ]. In addition, many cultivable salt-tolerant microbial strains isolated from saline environments survive under osmotic and ionic stresses and are known to mitigate the detrimental effects induced by a variety of abiotic stresses [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of plant growth promoting rhizobacteria (PGPR) has been widely exploited in the context of sustainable agricultural productivity [ 4 ]. Among various beneficial roles that PGPR confer to their host plant including production of growth enhancers, phytohormones, nutrient assimilation, metal chelation, they are also well known for their synthesis of surface-active compounds known as biosurfactants [ 5 , 6 , 7 ]. Biosurfactants are biomolecules that are amphiphilic in nature and include a large category of glycolipids, lipopeptides phospholipids, fatty acids and polymeric macromolecules [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%